Synthesis and biological evaluation of the natural product komaroviquinone and related compounds aiming at a potential therapeutic lead compound for high-risk multiple myeloma. Issue 19 (1st October 2017) - Suto, Yutaka; Sato, Mariko; Fujimori, Kota; Kitabatake, Shotaro; Okayama, Mikio; Ichikawa, Daiju; Matsushita, Maiko; Yamagiwa, Noriyuki; Iwasaki, Genji; Kiuchi, Fumiyuki; Hattori, Yutaka
Graphical abstract: Abstract: Alternatives of treatments for multiple myeloma (MM) have become increasingly available with the advent of new drugs such as proteasome inhibitors, thalidomide derivatives, histone deacetylase inhibitors, and antibody drugs. However, high-risk MM cases that are refractory to novel drugs remain, and further optimization of chemotherapeutics is urgently needed. We had achieved asymmetric total synthesis of komaroviquinone, which is a natural product from the plant Dracocephalum komarovi . Similar to several leading antitumor agents that have been developed from natural compounds, we describe the antitumor activity and cytotoxicity of komaroviquinone and related compounds in bone marrow cells. Our data suggested that komaroviquinone-related agents have potential as starting compounds for anticancer drug development.